2004
DOI: 10.1007/s00259-004-1565-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 131I-SPECT/CT images obtained with an integrated system in the follow-up of patients with thyroid carcinoma

Abstract: Integrated 131I-SPECT/CT was found to have an additional value over planar imaging in patients with thyroid cancer for correct characterization of equivocal tracer uptake seen on planar imaging as well as for precise localization of malignant lesions in the neck, chest, and skeleton. SPECT/CT optimized the localization of 131I uptake to lymph node metastases versus remnant thyroid tissue, to lung versus mediastinal metastases, and to the skeleton. It also had a further clinical impact on patient management by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(97 citation statements)
references
References 6 publications
4
85
0
8
Order By: Relevance
“…diagnostic value, compared with planar imaging, in 57% of the 71 patients with thyroid carcinoma in a retrospective study (22). At the same time, Ruf et al performed a prospective study and concluded that the addition of SPECT/CT improved the interpretation of inconclusive 131 I findings on planar scans after ablative radiotherapy (23).…”
Section: Discussionmentioning
confidence: 99%
“…diagnostic value, compared with planar imaging, in 57% of the 71 patients with thyroid carcinoma in a retrospective study (22). At the same time, Ruf et al performed a prospective study and concluded that the addition of SPECT/CT improved the interpretation of inconclusive 131 I findings on planar scans after ablative radiotherapy (23).…”
Section: Discussionmentioning
confidence: 99%
“…These datasets are typically displayed with cursor control so that they can easily be reviewed by the interpreting physician. Current clinical experiences have shown that the use of SPECT/CT provides the interpreting physician with a higher level of confidence in providing diagnostic information, and the presence of anatomic data from CT in fused images typically adds diagnostic information in 30%-35% of the cases, with even higher contributions in specific disease processes (11).…”
Section: Spect/ctmentioning
confidence: 99%
“…Tharp and cols. (5) found that the use of this hybrid imaging combination contributed to the immediate management of thyroid cancers in 25% of cases. It is usually not essential to have full diagnostic quality CT images to accurately place the uptake.…”
Section: Discussionmentioning
confidence: 99%